229k views
4 votes
Solving systems. x-y=2. y=4-2x

1 Answer

5 votes

We have the system of equations:


\begin{gathered} x-y=2 \\ y=4-2x \end{gathered}

We can solve by substitution, using the information already given by the second equation.

We can replace y in the first equation and solve for x:


\begin{gathered} x-y=2 \\ x-(4-2x)=2 \\ x-4+2x=2 \\ x+2x=2+4 \\ 3x=6 \\ x=(6)/(3) \\ x=2 \end{gathered}

Then, we can find y using the second equation as:


y=4-2x=4-2\cdot2=4-4=0

Answer: x=2 and y=0

User Calvin Park
by
6.0k points